Evaluation of Anti-Angiogenic Effect of Naturally Occurring Compound from Ficus.Bengalensis on Regeneration (Global Journal of Medical Research, 2015)
Angiogenesis is the process that leads to the formation of new blood vessels or neovascularisation. Angiogenesis inhibitors are designed to prevent the formation of new blood vessels. The main aim of this study is to evaluate Anthocyanin obtained from medicinal plant Ficus.bengalensis for Anti-angiogenesis
Keywords: anthocyanin; regenerative angiogenesis; vegf (vascular endothelial growth factor); zebrafish embryos (larvae)